2014
DOI: 10.1080/10408398.2011.645259
|View full text |Cite
|
Sign up to set email alerts
|

Yacon (Smallanthus Sonchifolius): A Food with Multiple Functions

Abstract: Functional foods are the focus of many studies worldwide. This is justified by the effects they have on public health and thus interest in elucidation of the mechanisms involved in their actions. The present review aims to broaden the discussions of the functional properties attributed to yacon (Smallanthus sonchifolius), considered a food with multiple functions since it possesses bioactive compounds (antimicrobial, antioxidant, and probiotic substances) that exert beneficial effects on the body. Although som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 53 publications
1
28
0
3
Order By: Relevance
“…The tuberous yacon roots may be considered a functional food by its content in FOS, a prebiotic which confers its functional properties, mostly related to the increase of lactobacilli and bifidobateria in the gut (Miyaguchi et al, 2015), and the resulting benefits for hyperglycemic and hyperlipidemic (high cholesterol) individuals. However, it should be consumed in moderate quantities (Sabater-Molina et al, 2009;Aluko, 2012;Mentreddy et al, 2007;Ojansivu et al, 2011;Choque et al, 2013;Almeida et al, 2015;Caetano et al, 2016). Side-effects like flatulence or diarrhoea might occur in individuals with dietary fructose intolerance because of the high levels of this sugar found in some yacon extracts.…”
Section: Yacon (Smallanthus Sonchifolius)mentioning
confidence: 99%
“…The tuberous yacon roots may be considered a functional food by its content in FOS, a prebiotic which confers its functional properties, mostly related to the increase of lactobacilli and bifidobateria in the gut (Miyaguchi et al, 2015), and the resulting benefits for hyperglycemic and hyperlipidemic (high cholesterol) individuals. However, it should be consumed in moderate quantities (Sabater-Molina et al, 2009;Aluko, 2012;Mentreddy et al, 2007;Ojansivu et al, 2011;Choque et al, 2013;Almeida et al, 2015;Caetano et al, 2016). Side-effects like flatulence or diarrhoea might occur in individuals with dietary fructose intolerance because of the high levels of this sugar found in some yacon extracts.…”
Section: Yacon (Smallanthus Sonchifolius)mentioning
confidence: 99%
“…They received recognition during the past two decades due to their nutritional, functional constitutes, and health beneficial effect. In particular, yacon tubers have high contents of bioactive compounds (e.g., phenolic compounds), fructooligosaccharides (FOS) and low sugar content [9,10]. On that account, yacon has gained attention as an interesting crop for production of functional foods with low sugar content [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, food processing such as drying, evaporation, and fermentation can be used to develop food products such as yacon chips, flour, syrup, vinegar, etc. to extend the shelf life of yacon tubers [9].…”
Section: Introductionmentioning
confidence: 99%
“…Samallanthus sonchifolius otherwise known as yacon, is widely cultivated worldwide and has been found to contain numerous carbohydrate and secondary metabolites. Several recent studies have demonstrated the medical benefits of yacon, which are related to its effects on various cellular signaling molecules [ 12 , 13 , 14 ]. However, none of these studies has yet established the effect of yacon on brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Yacon consists of diverse bioactive compounds that do not only induce physical health effects but also promote physiological responses. Yacon contains phytoalexins for antimicrobial activity, chlorogenic acids as antioxidant, anti-inflammation, anti-allergic, anti-cancer, and probiotic properties that counteract obesity and diabetes [ 12 , 13 , 14 , 18 , 19 , 20 ]. Although, it has been widely reported that yacon exhibits an anti-cancer effect, its therapeutic effect on gliomas remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%